2013
DOI: 10.1007/s10452-012-9424-x
|View full text |Cite
|
Sign up to set email alerts
|

Migration and habitat use of the tropical eels Anguilla marmorata and A. bicolor pacifica in Vietnam

Abstract: The patterns of use of marine and freshwater habitats by the tropical anguillid eels Anguilla marmorata and A. bicolor pacifica were examined by analysing the otolith strontium (Sr) and calcium (Ca) concentrations of yellow (immature) and silver (mature) stage eels collected in Vietnamese waters. In A. marmorata, the change in the Sr:Ca ratios outside the high Sr:Ca core was generally divided into three patterns: (1) typical catadromous life history pattern;(2) constant residence in brackish water; and (3) hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 24 publications
3
37
1
1
Order By: Relevance
“…However, the habitat preference differed among the sites (countries) (Figures and Table ). These findings indicate that the tropical A. bicolor bicolor and A. bicolor pacifica have a flexible migration strategy with a high degree of behavioural plasticity and an ability to utilise the full range of salinity similar to that of the tropical A. marmorata (Arai et al , ; Arai & Chino, ; Chino & Arai, ; Lin et al , ; Shiao et al , ) and the temperate A. japonica (Chino & Arai, ; Shiao et al , ; Tsukamoto & Arai, ; Tzeng et al ), A. anguilla (Arai et al , ; Shiao et al , ), A. rostrata (Jessop et al , ; Lamson et al , ), A. australis and A. dieffenbachii (Arai et al , ). These eels migrate flexibly among freshwater, brackish water and seawater environments.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, the habitat preference differed among the sites (countries) (Figures and Table ). These findings indicate that the tropical A. bicolor bicolor and A. bicolor pacifica have a flexible migration strategy with a high degree of behavioural plasticity and an ability to utilise the full range of salinity similar to that of the tropical A. marmorata (Arai et al , ; Arai & Chino, ; Chino & Arai, ; Lin et al , ; Shiao et al , ) and the temperate A. japonica (Chino & Arai, ; Shiao et al , ; Tsukamoto & Arai, ; Tzeng et al ), A. anguilla (Arai et al , ; Shiao et al , ), A. rostrata (Jessop et al , ; Lamson et al , ), A. australis and A. dieffenbachii (Arai et al , ). These eels migrate flexibly among freshwater, brackish water and seawater environments.…”
Section: Discussionmentioning
confidence: 89%
“…Sagittal otoliths were extracted from each fish, embedded in epoxy resin (Struers Epofix; http://www.struers.com) and mounted on glass slides. The otoliths were then ground and polished as described by Arai et al (). They were then cleaned in an ultrasonic bath and rinsed with deionized water prior to examination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, otolith microchemical analysis using G. maculatus revealed that diadromous individuals were only found in rivers with poor productivity, whereas no individuals seemed to move downstream in rivers with productive floodplains (Carrea et al ., ). Similarly, studies of tropical Anguilla spp., such as the Indian shortfin eel Anguilla bicolor pacifica (Schmidt 1928) demonstrated that >80% of individuals were considered to be estuarine residents (Arai et al ., ) and sometimes showed higher growth rates in saline waters than in freshwaters (Cairns et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the AUC values reported here are much lower than those for freshwater fish in other regions and indicate further work is required to accurately predict the response of the Fijian fish fauna to disturbances . For instance, we found that the occurrence rates of species with flexible habitat use (e.g., Anguilla spp., Arai, Chino and Le (2013)) and some species that were rarely recorded in the field surveys (e.g., Mugilogobius notospilus, & Glossogobius sp. 2) were poorly predicted by other species within the same trait or taxonomic group.…”
Section: Discussionmentioning
confidence: 99%